Tiny but mighty mayfly - probing Prosopistoma pennigerum (Müller 1785) as the Flagship species for the Vjosa Wild River National Park - Thea Schwingshackl; Jan Martini; Mourine Yegon; Gabriel Singer; Simon Vitecek (Journal of Insect Conservation, 2024)
The recently created Vjosa Wild River National Park sets precedence at the European scale to protect a rare river ecosystem and, at the same time, the last refuge of the almost extinct mayfly Prosopistoma pennigerum (Müller 1785, Fig. 1). We extensively searched for the species in the Vjosa and five abiotically similar but fragmented surrounding rivers. To characterize the genetic diversity of the Vjosa population and assess its potential as a source population, we analysed partial mtCOI data. Besides high abundances in the Vjosa River, we observed only a few specimens in the free-flowing section of the Osumi River, but in no other investigated river although suitable habitat appears to be widely available at site-scale. Molecular analysis of 174 specimens revealed largely homogeneous sequences across all sampling sites and an almost 100% infection rate with Wolbachia sp. that suggests parthenogenetic reproduction, possibly as a strategy to increase resilience to high natural disturbance dynamics. We argue that P . pennigerum should serve as a flagship species for the Vjosa Wild River National Park. The species is exceptionally aesthetic, and its most viable, but apparently parthenogenetic populations are restricted to the Vjosa River where the species is widespread. The restricted regional distribution indicates only weak (or no) potential to recolonize and/or re-establish in other rivers, and the absence from fragmented rivers suggests dependence on high ecological integrity. Implications for conservation: Our findings thus sanction our nomination of P . pennigerum as the flagship species for the Vjosa Wild River National Park.